(untitled) (Argos, 2025)
In this article, we propose to explore the complex web of meanings that classical Greek culture developed around ἔρως based on the moral and legal rules established for marriage and pederasty. We aim to demonstrate how the ancient Greeks problematized erotic bonds based on certain assumptions related to the positive, organizing, and creative power, as well as the negative, chaotic, and destructive power of ἔρως.